Case Report: Structural Changes in the Coronary Vessel Wall in a Patient With Incomplete Kawasaki Disease - Ishikawa, Takamichi; Uchiyama, Hiroki; Mogi, Satoshi; Ohtani, Hayato (Frontiers in Pediatrics, 2022)
Background: Kawasaki disease (KD) is an acute systemic vasculitis of infants and young children that affects medium-sized vessels. Conventional cardiac imaging techniques, such as cardiac catheterization, are useful for characterizing the coronary arterial lesion (CAL) size and luminal diameter of the diseased coronary artery segment in patients with KD, but there are limitations to the visualization of the detailed vascular anatomy. Optical coherence tomography (OCT) is a high-resolution intracoronary arterial imaging modality that can distinguish the three layers of the coronary arterial wall. Several studies have reported coronary artery wall abnormalities in KD patients with coronary arterial aneurysm or regressed aneurysm. However, there have been no reports on changes in the coronary artery wall in cases of incomplete KD without CAL. Case presentation: We herein report an 11-year-old girl with a history of incomplete KD without coronary arterial aneurysms. She had been diagnosed with perimembranous ventricular septal defect (VSD) after birth and had experienced incomplete KD at one year old. During her hospitalization for KD, she did not receive intravenous immunoglobulin (IVIG), because she did not meet the Harada score or criteria for treatment in patients with incomplete KD established by the American Heart Association. No dilatation or coronary artery aneurysm were observed on transthoracic echocardiography in the acute or follow-up period. At 11 years old, she received cardiac catheterization and coronary angiography (CAG) for the evaluation of a VSD and follow-up of KD. CAG demonstrated no aneurysm, dilatation, or significant stenosis of the coronary arteries. We performed an OCT study, which revealed the presence of intimal thickening, disruption of the media, and neovascularization in the left anterior descending artery. Conclusion: OCT demonstrates the structural changes of CA even in the patient with incomplete KD who have not been treated with IVIG.